Assessing Awareness and Implementation of Educational Technology and ICT Tools in Teaching at Selected Engineering Institutes in Western Maharashtra - Sunanda Mahesh Shinde; Mahesh Balasaheb Shinde (Scientia Publica Media, 2026)
The rapid advancement of educational technology (EdTech) and information and communication technology (ICT) has significantly transformed teaching–learning practices in engineering institutes, driven by the increasing demand for flexible, student-centred, and technology-enabled education. Although a wide range of digital tools is available, engineering faculty differ considerably in their awareness, adoption, and effective pedagogical integration of these technologies. In this context, the present study examines faculty awareness and use of EdTech and ICT tools in engineering education through a taxonomy-based framework that categorizes varying levels of technological awareness and instructional application. The primary objective of the study is to assess how engineering educators perceive, access, and utilize digital tools for instructional delivery, assessment, collaboration, and student engagement. A descriptive and analytical research design was employed, and data were collected from engineering faculty using structured questionnaires and reflective inputs. The awareness taxonomy was applied to systematically analyse faculty engagement with ICT tools, ranging from basic familiarity to advanced pedagogical integration. The study also explores the use of commonly adopted digital platforms, including learning management systems, virtual classrooms, collaborative applications, and multimedia resources, along with instructional approaches such as blended learning and flipped learning. The findings indicate that while a majority of faculty members demonstrate moderate to high awareness of EdTech tools, their effective classroom implementation is often constrained by limited training opportunities, time constraints, infrastructural limitations, and resistance to pedagogical change. Nevertheless, educators who actively integrated technology-enabled strategies reported higher levels of student engagement, improved collaboration, and enhanced learning outcomes. The study concludes that structured professional development initiatives, strong institutional support, and a clearly defined awareness framework are essential for achieving meaningful and sustainable integration of EdTech and ICT in engineering education. The insights from this study can inform educators, administrators, and policymakers in strengthening technology-driven teaching practices.